H2 In Situ Inducing Strategy on Pt Surface Segregation Over Low Pt Doped PtNi5 Nanoalloy with Superhigh Alkaline HER Activity. (29th January 2021) - Zhang, Cong; Liang, Xin; Xu, Ruinian; Dai, Chengna; Wu, Bin; Yu, Gangqiang; Chen, Biaohua; Wang, Xiaolei; Liu, Ning
Abstract: Surface segregation constitutes an efficient approach to enhance the alkaline hydrogen evolution reaction (HER) activity of bimetallic Pt x Ni y nanoalloys. Herein, a new strategy is proposed by utilizing the small gas molecule of H2 as the structure directing agent (SDA) to in situ induce Pt surface segregations over a series of PtNi5 ‐ n samples with extremely low Pt doping (Pt/Ni = 0.2). Impressively, the sample of PtNi5 ‐0.3 synthesized under 0.3 MPa H2 delivers an extremely low overpotential of 26.8 mV (−10 mA cm −2 ) and Tafel slope of 19.2 mV dec −1, which is superior to most of the previously reported Pt x Ni y electrocatalysts. This is substantially related to the strong H2 in situ inducing effect to generate Pt‐rich@Ni‐rich core‐shell nanostructure of PtNi5 ‐0.3 with an ultrahigh Pt surface content of 46%. The specific mechanistic effects of H2 during the PtNi5 ‐ n synthesis process are well illustrated based on the combined experimental and theoretical studies. The density functional theory mechanism simulations further unravel that the evolved active site of PtNi5 ‐ n can efficiently reduce the reaction Gibbs free energies; especially for the scenario of PtNi5 ‐0.3, the downward‐shifted d band center of the Pt active site significantly reduces the PtH bond strength, eventually resulting in the lowest absolute value of Δ G H . Abstract : A highly active PtNi5 ‐0.3 nanoalloy (26.8 mV at 10mA cm −2, Tafel slope of 19.2 mV dec −1 ) with an ultrahigh surface Pt content (46%) and extremely low Pt doping (Pt/Ni = 0.2) is successfully prepared based on a H2 in situ inducing strategy, wherein the H2 majorly functions in two aspects including kinetics (metal precursor reduction) and thermodynamics (surface free energy).